Effect of Child Friendly Constraint Induced Movement Therapy on Unimanual and Bimanual Function in Hemiplegia - Seyed Mohammad Sadegh Hosseini; Hossein Sourtiji; Atefeh Taghizadeh (Iranian Rehabilitation Journal, 2010)
Objectives: Hemiplegia is a non-progressive damage in premature growing brain which causes movement disorders in one side of the body. The objective of present research is to study the method of modified constraints induced movement therapy (CIMT) which can be appropriate on unimanual and bimanual functions of children with Hemiplegia.